Agrobacterium rhizogenes MTCC 532 Induced Hairy Root Development in Tephrosia purpurea (L) and its Effect on Production of Tephrosin - Dixit, A. K.; Vaidya, S.; Devaliya, R. (Journal of Scientific Research, 2012)
In Ayurvedic system of medicine T. purpurea is used as important drug for various ailments as tonic, laxative, anthelmintic, purifier of blood, a cordial, cough, asthma, tympanitis, dyspepsia, snake bite and in bilious febrile attacks enlargement and obstruction of the liver, spleen and kidneys. The roots are the sites of synthesis and/or storage of many plant metabolites and also an important organ for the production of valuable phytochemical. Roots of T. purpurea contain tephrosin, deguelin, isotephrosin and maxima substances which makes it important drug plant. Therefore, an attempt had been made to study the inoculation effect of Agrobacterium rhizogenes (MTCC- 532) on growth, development of hairy roots and its effect on production of secondary metabolites in T. purpurea roots. After transformation of A. rhizogene (MTCC-532) significant increment in fresh weight in hairy roots cultured in solidified media was observed, the data revealed 7.6 times more fresh weight from initial fresh weights. In inoculated roots fast initiation of hairy roots was observed. 1.528g tephrosin was obtained from 40g of roots of field grown plants, giving the concentration of tephrosin in field grown plants roots to 38.2 mg /g d.w.b. © 2012 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v4i3.8844 J. Sci. Res. 4 (3), 741-748 (2012)